HOÀN THIỆN THIẾT KẾ, CHẾ TẠO VÀ ÁP DỤNG THỬ MODUL ĐIỀU KHIỂN, KIỂM SOÁT NHIỆT ĐỘ VÀ MODUL K - Đồng, Phạm Khôi; Nguyễn, Phi Long; Nguyễn, Văn Bộ; Nguyễn, Như Hưng; Lê, Quỳnh Ngân; Lương, Xuân Tiến (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
COMPLETE DESIGN, MANUFACTURE AND TEST OF TEMPERATURE CONTROL AND CONNECTION SIGNALS MODULES OF LAVA BAROMETER EQUIPMENT This paper describes the research process to improve the tropical reliability of temperature control and connection signals modules of LAVA equipment and methods to testthe performance of the modules. The test results show that the modules fully meet all technical requirements and can be used when failure occurs.